A novel quaternary equiatomic Ti-Zr-Nb-Ta medium entropy alloy (MEA). (October 2018) - Nguyen, V.T.; Qian, M.; Shi, Z.; Song, T.; Huang, L.; Zou, J.
Abstract: The high strength and low ductility of body-centred cubic (BCC) high entropy alloys (HEAs) both result from the severe lattice-distortion effect as measured by the atomic mismatch ( δ ). We report a novel quaternary equiatomic Ti-Zr-Nb-Ta ( δ  = 4.8%) medium entropy alloy (MEA), redesigned from a quinary equiatomic Ti-Zr-Nb-Ta-Mo ( δ  = 5.5%) HEA, for much improved strength-ductility combinations and potentially improved biocompatibility by reducing δ through excluding Mo. The as-cast MEA exhibited a single BCC phase and achieved compressive yield strength of 1100 ± 90 MPa, strain of 48 ± 6%, which is 4 times higher than that of the Ti-Zr-Nb-Ta-Mo HEA, and modulus of 116 ± 6 GPa similar to Ti-6Al-4V. Highlights: A novel quaternary equiatomic Ti-Zr-Nb-Ta medium entropy alloy (MEA) was designed and fabricated. The novel MEA showed 4 times better ductility than the quinary equiatomic Ti-Zr-Nb-Ta-Mo high entropy alloy (HEA). The novel MEA has the same lattice structure as that of Ta or Nb and also very similar lattice parameters. Both the empirical rule and the Pandat™ tool were able to predict the phase formation in the MEA.